2016
DOI: 10.1002/jat.3325
|View full text |Cite
|
Sign up to set email alerts
|

Impact of silver nanoparticles on marine diatom Skeletonema costatum

Abstract: When silver nanoparticles (AgNPs) are used commercially at a large scale, they infiltrate the environment at a rapid pace. However, the impact of large quantities of AgNPs on aquatic ecosystems is still largely unknown. In aquatic ecosystems, the phytoplanktons have a vital ecological function and, therefore, the potential impact of AgNPs on the microalgae community has elicited substantial concern. Therefore, in this study, the impacts of AgNPs on a marine diatom, the Skeletonema costatum, are investigated, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(46 citation statements)
references
References 46 publications
3
41
1
1
Order By: Relevance
“…In aquatic environment, green algae and diatom are not only the primary producers for higher tropic levels but also play an important role for the normal functioning of aquatic ecosystems [10]. Numerous studies have demonstrated that NPs generated adverse effects on freshwater and marine microalgae species [3,[24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In aquatic environment, green algae and diatom are not only the primary producers for higher tropic levels but also play an important role for the normal functioning of aquatic ecosystems [10]. Numerous studies have demonstrated that NPs generated adverse effects on freshwater and marine microalgae species [3,[24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…In ecological ecosystems, the microalgae are primary producers and play a vital role in the food chains. us, the bad effects of pollutants on microalgae species may break the balance of whole ecosystems [10]. e toxic effect and behavior of nanomaterial in the ecosystems on microalgae have been recently reviewed [3,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The enhancement of biotic generation of antioxidant enzymes has been reported in Chattonella marina as a defence mechanism against the adverse effect of AgNPs on PS II, which may involve inhibition of electron transport activity and alteration of oxygen evolution [65] ; [20] ; [17]. Table (3 splendida showed lower biomass growth and lipid productivity, yield and content than the C. vulgaris.…”
Section: Effects Of Agnps On Microalgal Cell Growthmentioning
confidence: 97%
“…The use of trace or low nanoparticle concentrations has reportedly induced stimulation of algal biomass and pigment content with enhanced lipid production [11][12][13][14][15][16]. The effects of AgNPs on diatom Skeletonema costatum [17], Thalassiosira pseudonana and Cyanobacterium synechococcus sp. [18] and the eukaryotic green algae [6] have been reported.…”
Section: Introductionmentioning
confidence: 99%